Integrating Islamic Moderation Values in Teaching Speaking through Group Activity - Achmad Baidawi; Wahab Syakhirul Alim; Rabi'ah Rabi'ah (Institut Agama Islam Negeri Madura, 2020)
Instilling Islamic moderation values is done to respond to the coming of some people bringing radicalism which is considered to disturb the peace and harmony of the social life of Indonesian people. Islamic moderation is a response to radicalism that must be implanted and infected to young generations. This research was intended to know how Islamic moderation values were implanted and what Islamic moderation values were implemented in teaching speaking through group work activity. This research used descriptive qualitative field research. The data collection instruments were observation and interview. The steps of data analysis were data condensation, data display, and conclusion drawing. This research revealed that the lecturer employed group work activity. In group work activities, the students were divided into seven groups. The member of the group consisted of five or six students. Each student in the group had their roles such as a master of ceremony, moderator, and presenter. In playing their role, they respected one and another. They discussed the topic within the group. No one dominated. After doing a discussion within the group, then each group had their turns to present their topic. If one group were presenting, the rest became the audience and vice versa. Therefore, Islamic moderation values such as Syura (discussion), Tasamuh (tolerant), Tathawur wa Ibtikar (dynamic, creative, and innovative), and Musawah (egalitarian) were implanted and implemented through group work activity in teaching speaking